(untitled) (International Journal of Current Engineering and Technology, 2014)
In a developing country like India, The struggle to get power is maximum, here is an attempt to generate the power in normal one way road by design based power generation similar to a speed breaker concept. The mechanism is very simple, a constrained inclined plate is used instead of a road hump which can create a to and fro motion if the spring is attached to it. The to and fro motion is converted into the kinetic energy of the flywheel by using a ball bearing and hence electrical power can be generated using that rotational energy. The power generated is considerably large as compared to other small scale renewable energy resources per square area and hence can be successfully implemented in daily life to generate power. From this the scarcity of the power to lit up can be reduced.